1984
DOI: 10.1002/ar.1092090315
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in pituitary thyrotropes of the hibernating bat Myotis lucifugus lucifugus: An immunohistochemical study

Abstract: Pituitary thyrotropes were identified throughout the year in the hibernating bat Myotis lucifugus lucifugus by means of light microscopic immunohistochemistry. These cells occupied a small proportion of the volume of the pars distalis (mean = 1.36% in males; mean = 1.52% in females) and exhibited a limited distribution pattern that was characteristic of all animals examined. Cells that were immunoreactive with an antiserum directed against the beta subunit of thyroid-stimulating hormone were most numerous in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Seasonal variations studies of the thyrotroph cells number and cellular activity carried out in woodchuck ( Marmota monax ) have shown that these parameters vary according to the thyroid gland activity and the animal physiological activities (Frink et al, 1980). A higher proportion of these cells in June after hibernation and a lower proportion in December during mating were observed in bat (Anthony and Gustafson, 1984). This finding suggests that the increase of thyrotrophs frequency in spring coincides with a metabolic activity increase and also with early stages of the spermatogenesis.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Seasonal variations studies of the thyrotroph cells number and cellular activity carried out in woodchuck ( Marmota monax ) have shown that these parameters vary according to the thyroid gland activity and the animal physiological activities (Frink et al, 1980). A higher proportion of these cells in June after hibernation and a lower proportion in December during mating were observed in bat (Anthony and Gustafson, 1984). This finding suggests that the increase of thyrotrophs frequency in spring coincides with a metabolic activity increase and also with early stages of the spermatogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…The localization and morphology of PD TSH cells were studied in species such as monkey (Girord and Trouillas, 1980), bat (Anthony and Gustafson, 1984; Mikami et al, 1988), rat (Kum et al, 2006), toad (Miranda et al, 1996), and bullfrog (Tanaka et al, 1990), and the results show a similar distribution pattern in different species. It is interesting to point out that the TSH cells are generally restricted to the PD anterior and medial zones, and they are rarely observed in the dorsal region next to pars intermedia (PI).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most findings on the function of hormoneproducing cells have been made using immunohistochemistry with heterologous antisera as follows. During the arousal period, thyrotrophs show the increased activity (Anthony and Gustafson, 1984b). Annual changes in corticotrophs are related to the so-called fat cycle in tropical vespertilionid bats (Singh and Krishna, 1996b).…”
Section: (1) Pars Distalismentioning
confidence: 99%